HOPE is a good thing? Probationer perceptions of and experiences with the honest opportunity probation with enforcement demonstration field experiment - Zajac, Gary (Journal of crime and justice, 2021)
This article examines how the Honest Opportunity Probation with Enforcement (HOPE) program was received by probationers in the context of a large-scale replication and evaluation trial. The HOPE DFE found mostly null effects from HOPE, begging the question of why this popular intervention failed to deliver desired results. Computer assisted interviews with nearly 1,000 HOPE and control probationers and open ended in-person interviews with 21 HOPE probationers suggest that HOPE may have been better received by probationers who were less entrenched in criminal thinking and attitudes and who were more motivated to avoid ongoing consequences of antisocial behavior. HOPE may have struggled with probationers who were indifferent to or dismissive of the rigid sanctioning strategy delivered by HOPE.